CASE REPORT A 30-year-old Woman with Multiple-Sites Metastasis Lung Adenocarcinoma and Coronavirus-19 Disease (COVID-19) - Naftali, Yokanan; Sugiri, Jani Jane Rosihaningsih; Pratiwi, Suryanti Dwi; Yudhanto, Hendy Setyo (Malang Respiratory Journal, 2022)
Background: Adenocarcinoma is the most common Non-Small Cell Lung Cancer (NSCLC) in non-smokers in Indonesia. It often metastasizes in multiple sites. Metastasis is a negative predictor for prognosis in lung adenocarcinoma. In this covid pandemic era we present a case of a 30-years-old woman with adenocarcinoma and multiple-sites metastasis, and Coronavirus-19 Disease (COVID-19). Case: A 30-year-old woman came to our hospital with multiple complaints of hearing loss, visual loss, and occasional shortness of breath. The patient had a history of wild-type EGFR adenocarcinoma and has been treated with 4 cycles of gemcitabine. She also presented with a lump in her neck. Further examination revealed multiple metastasis tumours in her brain, right eye, neck, and spine. Pleural fluid examination also showed a malignant pleural effusion. Nasopharyngeal swab using reverse transcriptase-polymerase chain reaction (rt-PCR) method revealed that she also suffers from COVID-19 with positive swab result. Despite adequate treatment, she rapidly deteriorates and passed away in hospital. Discussion: Management in this patient is complex due to multiple complications and limitation of management given in COVID-19 isolation ward. She presented with multiple equally complicated metastasis, in which treatment priority should be carefully assessed. Despite treatment by multiple specialists, her problems still persist and proved to be fatal. Conclusion: Although metastasis is common in adenocarcinoma, multiple metastasis is uncommon, and this case highlights the need of careful management priority in such patients in COVID-19 pandemic setting. Keywords: Adenocarcinoma, Multiple Metastasis, Lung Cancer, COVID-19